The ankle kinematic reference of normal gait pattern in Thai adults - Klaewkasikum, Krongkaew; Patathong, Tanyaporn; Angsanuntsukh, Chanika; Woratanarat, Thira; Sanguantrakul, Jongsook; Woratanarat, Patarawan (Frontiers in Surgery, 2022)
Objective This study was aimed to establish the reference values of ankle kinematics and factors associated with ankle kinematics of healthy Thai adults. Methods A prospective cohort was conducted among healthy volunteers aged between 18 and 40 years and evaluated gait analysis between 2016 and 2020. After applying the modified Halen Hayes marker set, participants were assigned to walk 8–10 rounds with their preferred speed. Demographic data i.e., age, gender and body mass index (BMI) and ankle kinematics (varus-valgus, dorsiflexion-plantar flexion, foot progression, and ankle rotation) using motion analysis software were recorded and analyzed. Results 98 volunteers (60 females and 38 males) aged 28.6 ± 5.4 years with body mass index 21.2 ± 2.0 kg/m2 were included. The average ranges of ankle kinematics entire gait cycle were varus-valgus −1.62 to 3.17 degrees, dorsiflexion-plantar flexion 0.67 to 14.52 degrees, foot progression −21.73 to −8.47 degrees, and ankle rotation 5.22 to 9.74 degrees. The ankle kinematic data in this study population was significantly different from the normal values supplied by OrthoTrak software of the motion analysis program, especially more ankle internal rotation at mid-stance (5.22 vs. −12.10 degrees) and terminal stance (5.48 vs. −10.74 degrees) with P < 0.001. Foot progression significantly exhibited more external rotation for 1.5 degrees on the right compared to the left side, and for 5 degrees more in males than females. One increment in age was significantly correlated with ankle internal rotation at mid-swing (coefficient 0.21 degrees, P = 0.039). BMI had no statistical association with ankle kinematics. Statistical parametric mapping for full-time series of angle assessments showed significantly different foot progression at initial contact and terminal stance between sides, and our ankle kinematics significantly differed from the reference values of the motion analysis program in all planes (P < 0.05). Conclusion The reference of ankle kinematics of Thai adults was established and differences between sides and the normal values of the motion analysis program were identified. Advanced age was associated with ankle internal rotation, and male gender was related to external foot progression. Further studies are needed to define all-age group reference values.